2022
DOI: 10.12928/pharmaciana.v12i1.20903
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant activity of Zingiber officinale, Hibiscus sabdariffa, and Caesalpinia sappan combination

Abstract: Medicinal plants have been used in traditional treatment since a long time ago by local people in Indonesia. Nowadays, the trend in the consumption of medicinal plants, especially herbal drinks, is increasing. Zingiber officinale, Hibiscus sabdariffa, and Caesalpinia sappan are their main materials of medicinal plants. They were chosen because of their high antioxidant contents. Nevertheless, there is no scientific research on the antioxidant activity of the combination of the three extracts. Therefore, the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…34 In contrast to research by Widyapuspa et al, who reported that red ginger ethyl acetate extract had an IC50 value of 51.36 ± 0.05. 51 Red ginger's antioxidant activity is linked to its total flavonoid and phenolic content. This activity is attributed to the ability of these compounds to donate electrons or hydrogen to free radicals.…”
Section: Analysis Of the Antioxidant Activity Of Red Ginger Rhizome A...mentioning
confidence: 99%
“…34 In contrast to research by Widyapuspa et al, who reported that red ginger ethyl acetate extract had an IC50 value of 51.36 ± 0.05. 51 Red ginger's antioxidant activity is linked to its total flavonoid and phenolic content. This activity is attributed to the ability of these compounds to donate electrons or hydrogen to free radicals.…”
Section: Analysis Of the Antioxidant Activity Of Red Ginger Rhizome A...mentioning
confidence: 99%
“…Nilai aktivitas FRAP (%) sejalan dengan jumlah Fe 2+ yang terbentuk dari proses reduksi oleh infusa sampel uji. Dibandingkan pada penelitian terdahulu, ekstrak etil asetat Rosella memiliki aktivitas antioksidan menggunakan metode DPPH dengan nilai IC50 83,37 ppm (Widyapuspa et al, 2022), sedangkan berdasarkan penelitian dari (Widowati et al, 2022) bunga telang memiliki aktivitas FRAP dengan nilai IC50 5,56%. Daun Stevia memiliki inhibisi sebesar 62,681 % dengan metode DPPH (Garcia-Mier et al, 2021).…”
Section: Hasil Dan Pembahasanunclassified
“…Senyawa fenolik dan flavonoid, memiliki aktivitas antioksidan melalui mekanisme donor hidrogen sebagai agen pereduksi, quenching oksigen singlet, berperan sebagai kelator radikal bebas (Skroza et al, 2022). Berdasarkan jumlah senyawa flavonoid total pada ekstrak etil asetat bunga Rosella sebesar 24,81 mg QE (Quersetin Equivalent) /gram ekstrak (Widyapuspa et al, 2022) lebih besar dibandingkan jumlah senyawa flavonoid total pada bunga telang yaitu 4,88 g QE (Quersetin Equivalent) /100% (Widowati et al, 2022). Hal ini sejalan dengan aktivitas FRAP bunga Rosella yang pada penelitian ini lebih besar dibandingkan bunga Telang.…”
Section: Hasil Dan Pembahasanunclassified
“…Many researchers studied about the combination polyherbal about ginger, lemongrass, and mangsian. The combination of ginger and sappan wood also increases antioxidant activity better than being separated reported (Widyapuspa et al, 2022). The analgesic and anti-inflammatory activity of a combination of Phyllanthus reticulatus and Mimosa pigra (Akhter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%